Active control of milling chatter considering the coupling effect of spindle-tool and workpiece systems. (15th April 2022) - Li, Denghui; Cao, Hongrui; Chen, Xuefeng
Graphical abstract: Highlights: The coupling effect between the spindle-tool system and the workpiece system with similar characteristics is analyzed. Stability of the spindle-tool-workpiece (STW) system proves to be weaker than that of the spindle-tool or workpiece system. The necessity of chatter control based on the STW coupling system instead of the spindle-tool system is verified. Two active chatter control strategies for the STW system are proposed and experimentally verified. The maximum material removal rate is significantly improved under control. Abstract: Chatter occurred in the machining process can seriously limit the processing efficiency and reduce the surface quality of the machined workpiece, which urgently needs to be controlled. Aiming at milling of flexible workpieces with similar characteristics to the spindle-tool system, two active chatter control strategies are proposed in this work. Firstly, considering the coupling effect of the spindle-tool system and the workpiece system, the milling force is developed based on the regenerative effect. And the 3D stability lobe diagram along the tool path is constructed. Then, an active chatter control structure is designed by integrating piezoelectric actuators and displacement sensors into the spindle-tool-workpiece (STW) system. Next, based on the developed milling force and active control structure, two chatter control strategies with different feedback signals are proposed using the model predictive control method. Finally, numerical simulations and milling experiments are carried out under different cutting conditions. The results show that milling chatter of the STW system can be effectively controlled by the proposed strategies. The maximum material removal rate is also significantly improved.